ZONEAMENTO TIPO-MORFOLÓGICO: DISCUSSÕES PRELIMINARES NOS TERRITÓRIOS HABITACIONAIS DE FOZ DO IGUAÇU - PR - BRASIL - Ramme, Juliana; Pina, Silvia A. Mikami G. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Zoning is one of the most used mechanisms in the practice of urban planning and it is based, most of the time, on a single criterion: land use, thus called functional zoning. In Foz do Iguaçu it is no different. The City Hall Director Plans approved up to now have used this type of zoning as a model for territorial planning. Therefore, the objective of this article is to analyze the urbanistic guidelines to land use and land utilization that directed the implementation of the master plans in Foz do Iguaçu between the years of 2006 and 2015. This analysis intends to initiate a debate about the need of applying a morphological-type zoning with the purpose of increasing social justice and inhibiting unwanted urban transformation processes.